Case of anal fistula with Fournier's gangrene in an obese type 2 diabetes mellitus patient. Issue 2 (31st July 2015) - Yoshino, Hiroshi; Kawakami, Kyoko; Yoshino, Gen; Sawada, Katsuhiro
Abstract: A 64‐year‐old man was admitted to Shin‐suma General Hospital, Kobe, Japan, complaining of a 3‐day history of scrotal swelling and high fever. He had type 2 diabetes mellitus. On examination, his body temperature had risen to 38.5°C. Examination of the scrotum showed abnormal enlargement. Laboratory data were as follows: white cell count 35, 400/μL and glycated hemoglobin 9.6%. Anal fistula was found in an endorectal ultrasound. Computed tomography scan showed a relatively high density of subcutaneous tissue and elevated air density. Thus, he was diagnosed with Fournier's gangrene. On the fourth hospital day, the patient underwent debridement of gangrenous tissue. Seton surgery was carried out for anal fistula on the 34th hospital day. He responded to the treatment very well. He was discharged on the 33rd postoperative day. Once Fournier's gangrene has been diagnosed, considering the association of anal fistula and perianal abscess is important. Abstract : We present the case of an obese diabetic patient with Fournier's gangrene. Earlier detection and intervention may provide opportunities to improve outcomes Fournier's gangrene.